2015
DOI: 10.1542/peds.2015-1757
|View full text |Cite
|
Sign up to set email alerts
|

IgE Immunoadsorption Knocks Down the Risk of Food-Related Anaphylaxis

Abstract: The effects of an immunoadsorption procedure, specifically designed to remove immunoglobulin E (IgE), on food-induced anaphylaxis have never been evaluated. We evaluate the effects of IgE removal on the allergic thresholds to foods. A 6-year-old boy with anaphylaxis to multiple foods and steroid-resistant unstable allergic asthma displayed serum IgE levels of 2800 to 3500 kU/L. To lower IgE serum concentrations, which could be overridden by a high dose of omalizumab, 1.5 plasma volumes were exchanged in 8 aphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…In these highly selected patients, we found thresholds of 116.3 and 128.3 mg protein for milk and egg at DBPCFC. As in previous studies these thresholds ranged between 0.6 and 150 mg for milk and between 0.65 and 200 mg for egg [27], our patients severely allergic to baked foods do not present thresholds inferior to those allergic to milk/egg, confirming previous data [13,28,29].…”
Section: Discussionsupporting
confidence: 92%
“…In these highly selected patients, we found thresholds of 116.3 and 128.3 mg protein for milk and egg at DBPCFC. As in previous studies these thresholds ranged between 0.6 and 150 mg for milk and between 0.65 and 200 mg for egg [27], our patients severely allergic to baked foods do not present thresholds inferior to those allergic to milk/egg, confirming previous data [13,28,29].…”
Section: Discussionsupporting
confidence: 92%
“…In the recent years, immunoadsorption (IA) has evolved as an alternative anti-IgE treatment for patients with severe AD displaying high total serum IgE ( 4 9 ). In addition, it has been reported that IA can increase the threshold of IgE immunoreactivity to different food allergens and thus reduce the risk of anaphylaxis in multiple food allergy ( 10 , 11 ). Most recently, a pilot study indicated that IA may also be used to treat patients with allergic asthma ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…An equivalent strategy already was successfully applied in a child suffering from severe asthma (Kerzel et al, 2011), in patients with severe atopic dermatitis (Zink et al, 2016) and in a case of life-threatening food allergy (Dahdah et al, 2015). However, reduction of total IgE-levels in these patients was achieved either by plasma exchange (Kerzel et al, 2011), a very cumbersome and unspecific treatment, by using an adsorber non-specifically removing antibodies of all isotypes (Zink et al, 2016) or by an IgE-specific adsorber that also reduced IgG, IgM and IgA by approximately 40% (Dahdah et al, 2015). In contrast, IgE-depletion with IgEnio would facilitate Omalizumab administration after fewer desorptions and without alteration of other plasma components than IgE which would allow to use IgEnio also in children.…”
Section: Discussionmentioning
confidence: 99%